{-# LANGUAGE FlexibleContexts #-} {-# LANGUAGE FlexibleInstances #-} {-# LANGUAGE Safe #-} {-# LANGUAGE ScopedTypeVariables #-} {-# LANGUAGE TypeApplications #-} module Data.Lattice.Property where import safe Data.Lattice import safe Data.Order.Property import safe Data.Order.Syntax import safe Prelude hiding (Bounded, Eq (..), Ord (..), not) heyting0 :: Heyting a => a -> a -> a -> Bool heyting0 x y z = x /\ y <= z <=> x <= y // z heyting1 :: Heyting a => a -> a -> a -> Bool heyting1 x y z = x // y <= x // (y \/ z) heyting2 :: Heyting a => a -> a -> a -> Bool heyting2 x y z = (x \/ z) // y <= x // y heyting3 :: Heyting a => a -> a -> a -> Bool heyting3 x y z = x <= y ==> z // x <= z // y heyting4 :: Heyting a => a -> a -> a -> Bool heyting4 x y z = (x /\ y) // z == x // y // z heyting5 :: Heyting a => a -> a -> a -> Bool heyting5 x y z = x // (y /\ z) == x // y /\ x // z heyting6 :: Heyting a => a -> a -> Bool heyting6 x y = y <= x // (x /\ y) heyting7 :: Heyting a => a -> a -> Bool heyting7 x y = x /\ x // y == x /\ y heyting8 :: forall a. Heyting a => a -> Bool heyting8 _ = neg bottom == top @a && neg top == bottom @a heyting9 :: Heyting a => a -> a -> Bool heyting9 x y = neg x \/ y <= x // y heyting10 :: Heyting a => a -> a -> Bool heyting10 x y = x <= y <=> x // y == top heyting11 :: Heyting a => a -> a -> Bool heyting11 x y = neg (x \/ y) <= neg x heyting12 :: Heyting a => a -> a -> Bool heyting12 x y = neg (x // y) == neg (neg x) /\ neg y heyting13 :: Heyting a => a -> a -> Bool heyting13 x y = neg (x \/ y) == neg x /\ neg y heyting14 :: Heyting a => a -> Bool heyting14 x = x /\ neg x == bottom heyting15 :: Heyting a => a -> Bool heyting15 x = neg (neg (neg x)) == neg x heyting16 :: Heyting a => a -> Bool heyting16 x = neg (neg (x \/ neg x)) == top -- Double negation is a monad. heyting17 :: Heyting a => a -> Bool heyting17 x = x <= neg (neg x) coheyting0 :: Coheyting a => a -> a -> a -> Bool coheyting0 x y z = x \\ y <= z <=> x <= y \/ z coheyting1 :: Coheyting a => a -> a -> a -> Bool coheyting1 x y z = x \\ y >= (x /\ z) \\ y coheyting2 :: Coheyting a => a -> a -> a -> Bool coheyting2 x y z = x \\ (y /\ z) >= x \\ y coheyting3 :: Coheyting a => a -> a -> a -> Bool coheyting3 x y z = x >= y ==> x \\ z >= y \\ z coheyting4 :: Coheyting a => a -> a -> a -> Bool coheyting4 x y z = z \\ (x \/ y) == z \\ x \\ y coheyting5 :: Coheyting a => a -> a -> a -> Bool coheyting5 x y z = (y \/ z) \\ x == y \\ x \/ z \\ x coheyting6 :: Coheyting a => a -> a -> Bool coheyting6 x y = x >= x \\ y coheyting7 :: Coheyting a => a -> a -> Bool coheyting7 x y = x \/ y \\ x == x \/ y coheyting8 :: forall a. Coheyting a => a -> Bool coheyting8 _ = non bottom == top @a && non top == bottom @a coheyting9 :: Coheyting a => a -> a -> Bool coheyting9 x y = x /\ non y >= x \\ y coheyting10 :: Coheyting a => a -> a -> Bool coheyting10 x y = x >= y <=> y \\ x == bottom coheyting11 :: Coheyting a => a -> a -> Bool coheyting11 x y = non (x /\ y) >= non x coheyting12 :: Coheyting a => a -> a -> Bool coheyting12 x y = non (y \\ x) == non (non x) \/ non y coheyting13 :: Coheyting a => a -> a -> Bool coheyting13 x y = non (x /\ y) == non x \/ non y coheyting14 :: Coheyting a => a -> Bool coheyting14 x = x \/ non x == top coheyting15 :: Coheyting a => a -> Bool coheyting15 x = non (non (non x)) == non x coheyting16 :: Coheyting a => a -> Bool coheyting16 x = non (non (x /\ non x)) == bottom -- Double co-negation is a co-monad. coheyting17 :: Coheyting a => a -> Bool coheyting17 x = x >= non (non x) coheyting18 :: Coheyting c => c -> Bool coheyting18 x = x == boundary x \/ (non . non) x -- Leibniz rule coheyting19 :: Coheyting a => a -> a -> Bool coheyting19 x y = boundary (x /\ y) == (boundary x /\ y) \/ (x /\ boundary y) coheyting20 :: Coheyting a => a -> a -> Bool coheyting20 x y = boundary (x \/ y) \/ boundary (x /\ y) == boundary x \/ boundary y -- -- x '\\' x = 'top' -- x '/\' (x '\\' y) = x '/\' y -- y '/\' (x '\\' y) = y -- x '\\' (y '\\' z) = (x '/\' y) '\\' z -- x '\\' (y '/\' z) = (x '\\' y) '/\' (x '\\' z) -- 'neg' (x '/\' y) = 'neg' (x '\/' y) -- 'neg' (x '\/' y) = 'neg' x '/\' 'neg' y -- (x '\\' y) '\/' x '<=' y -- y '<=' (x '\\' x '/\' y) -- x '<=' y => (z '\\' x) '<=' (z '\\' y) -- x '<=' y => (x '\\' z) '<=' (y '\\' z) -- x '<=' y <=> x '\\' y '==' 'top' -- x '/\' y '<=' z <=> x '<=' (y '\\' z) <=> y '<=' (x '\\' z) -- -- -- adjointL $ ConnL (\x -> y \\ not x) (\z -> not z // not y) symmetric1 :: Biheyting a => a -> Bool symmetric1 x = neg x <= non x symmetric2 :: Symmetric a => a -> Bool symmetric2 x = (neg . neg) x == (converseR . converseL) x symmetric3 :: Symmetric a => a -> Bool symmetric3 x = (non . non) x == (converseL . converseR) x symmetric4 :: Symmetric a => a -> Bool symmetric4 x = non x == (converseL . not) x && neg x == (not . converseL) x symmetric5 :: Symmetric a => a -> Bool symmetric5 x = non x == (not . converseR) x && neg x == (converseR . not) x symmetric6 :: Heyting a => a -> Bool symmetric6 x = neg x \/ neg (neg x) == top symmetric7 :: Symmetric a => a -> a -> Bool symmetric7 x y = not (x /\ y) == not x \/ not y symmetric8 :: Symmetric a => a -> a -> Bool symmetric8 x y = (not . not) (x \/ y) == not (not x) \/ not (not y) symmetric9 :: Symmetric a => a -> a -> Bool symmetric9 x y = not (x \/ y) == not x /\ not y symmetric10 :: Symmetric a => a -> a -> Bool symmetric10 x y = converseL (x \/ y) == converseL x \/ converseL y symmetric11 :: Symmetric a => a -> a -> Bool symmetric11 x y = converseR (x /\ y) == converseR x /\ converseR y symmetric12 :: Symmetric a => a -> a -> Bool symmetric12 x y = converseL (x /\ y) == (non . non) (converseL x /\ converseL y) symmetric13 :: Symmetric a => a -> a -> Bool symmetric13 x y = converseR (x \/ y) == (neg . neg) (converseR x \/ converseR y) boolean0 :: Biheyting a => a -> Bool boolean0 x = neg x == non x boolean1 :: Heyting a => a -> Bool boolean1 x = neg (neg x) == x boolean2 :: Heyting a => a -> Bool boolean2 x = x \/ neg x == top boolean3 :: Coheyting a => a -> Bool boolean3 x = x /\ non x == bottom boolean4 :: Heyting a => a -> a -> Bool boolean4 x y = (x <= y) // (neg y <= neg x) boolean5 :: Biheyting a => a -> a -> Bool boolean5 x y = x \\ y == neg (neg y // neg x) boolean6 :: Biheyting a => a -> a -> Bool boolean6 x y = x // y == non (non y \\ non x)